2008
DOI: 10.1063/1.2981795
|View full text |Cite
|
Sign up to set email alerts
|

Entropy driven key-lock assembly

Abstract: The effective interaction between a sphere with an open cavity (lock) and a spherical macroparticle (key), both immersed in a hard sphere fluid, is studied by means of Monte Carlo simulations. As a result, a 2d map of the key-lock effective interaction potential is constructed, which leads to the proposal of a self-assembling mechanism: there exists trajectories through which the key-lock pair could assemble avoiding trespassing potential barriers. Hence, solely the entropic contribution can induce their self-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 25 publications
5
60
0
Order By: Relevance
“…Nevertheless, the types and strength of the bonds formed between the protein and ligand contribute to the binding affinity. Our speculation is in line with the recent study by Odriozola and coworkers (Odriozola et al, 2008), who showed that the key-lock assembly is solely driven by the entropic contribution even in the absence of attractive forces, pointing out the importance of solvent contribution in the underlying mechanisms of substrate-protein assembly processes.…”
Section: Enthalpy-driven Entropy-driven or Their Combination?supporting
confidence: 75%
“…Nevertheless, the types and strength of the bonds formed between the protein and ligand contribute to the binding affinity. Our speculation is in line with the recent study by Odriozola and coworkers (Odriozola et al, 2008), who showed that the key-lock assembly is solely driven by the entropic contribution even in the absence of attractive forces, pointing out the importance of solvent contribution in the underlying mechanisms of substrate-protein assembly processes.…”
Section: Enthalpy-driven Entropy-driven or Their Combination?supporting
confidence: 75%
“…Since then, the concepts related to depletion have been widely applied to various scientific fields [34]: in biology by interpreting phenomena like macromolecular crowding [35] and protein crystallization [36]; in nanotechnology through e.g. the development of self-assembly processes as key-lock structures [37,38]; in condensed matter physics, furnishing answers to fundamental problems like the condition for gas-liquid phase separation [39], the kinetics of crystallization [40,41] and the nature of glassy states [42]. More recently, the liquid crystal phase behavior of non-spherical colloids, typically rods [43][44][45][46][47][48] and plates [49][50][51][52], in presence of a depletant has also been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] In the present work, we assume cylindrical shape both for the key particle and for the lock cavity. In particular, the key particle is assumed to be a cylinder of radius R k and height H, while the lock cavity is characterized by radius R l and depth D. The conditions R k = R l and H = D correspond to the perfect size matching between lock and key.…”
Section: Microscopic Model and Theorymentioning
confidence: 99%
“…[2,3] As such, these model systems have recently received substantial attention both experimentally [2,3] and theoretically. [4][5][6][7][8] In a recent experimental study, [2] an efficient method has been developed to produce colloidal lock particles containing a spherically shaped cavity. The interaction between these lock particles and complementary spherical key particles is comprised of two major contributions: Coulomb repulsion arising due to charge stabilization, and depletion attraction [9] due to the presence of the polymeric depletants in solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation